Biometric parameters and intra ocular lens power used for cataract eyes in Karnali, Nepal - Baral, Pawan; Baral, Nabin; Maharjan, Indra Man; Gautam, Bhoj Raj; Bhandari, Madhavendra (Nepalese Journal of Ophthalmology, 2014)
Introduction: The biometric parameters of the eye are measured for the calculation of the intra ocular lens power to be used in cataract surgery. Objective: To report the keratometry reading, axial length and intra ocular lens power used for eyes operated for cataract in Karnali Zone, Nepal, and to compare these findings with those reported in other similar studies. Subjects and methods: The data for the study were retrospectively collected from the case files of patients who had undergone cataract surgery between January 2011 and July 2012 in Karnali Zone, Nepal. These surgeries were performed in an outreach surgical camp organized by the Himalaya Eye Hospital, Nepal, as a part of its annual program. The SPSS 16.0 and Microsoft Excel 2007 software were used for the data analysis. Results: The total number of patients taken for the study was 1055 and the total number of eyes was 1055. There were 530 (50.23%) males and 525 (49.77%) females, with the mean age of 64.34±11.25, ranging from 8 to 98 years.The mean keratometry reading for the total sample was 44.11±1.6 (range, 34.00D to 49.00D). The mean axial length for the total sample was 22.68±0.88 (range, 17.75 to 26.17). The mean IOL power for the total sample was 21.60±1.74 (range, +15.00 to +30.00). Conclusion: The biometric eye parameters of keratometry, axial length and IOL power of this study required for cataract surgery in a Karnali population are similar to those presented in other similar studies from Nepal and abroad. DOI: http://dx.doi.org/10.3126/nepjoph.v6i2.11690 Nepal J Ophthalmol 2014; 6(12): 192-196